Model Pembinaan Kemandirian Ibadah Santri di Pesantren Modern Misbahul Ulum Paloh Lhokseumawe - Sagala, Hairun Hasanah; Nasution, Muhammad Hasan (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
This study examines the strategies teachers (asātiżah) employed in fostering the worship independence of santri at Pesantren Modern Misbahul Ulum (PMMU). This study aims to analyze the approaches teachers use to enhance santri's worship independence and evaluate the effectiveness of these strategies. A qualitative approach with a case study method was employed, utilizing non-participatory observation, in-depth interviews, and documentation within the pesantren environment. The findings reveal that although PMMU faced various challenges, such as the diverse family backgrounds of the santri and difficulties in enforcing discipline, it successfully designed an effective coaching model. This model includes regulating worship schedules, promoting worship habituation, exemplifying teacher behavior, involving student organizations, and maintaining continuous supervision. Additionally, the application of a reward-and-punishment approach and an adaptation program for santri from different backgrounds proved effective in fostering greater adaptability and consistency in worship practices. Strategies such as grouping students based on age and ability, alongside a humanistic approach to discipline, significantly contributed to the development of santri's worship independence. This study recommends the integration of simple technological tools to support worship guidance and strengthen collaboration between teachers and parents.